From fish fin injury to Mycobacteroides abscessus: precision diagnosis in a complex case using shotgun metagenomics - Zainulabid, Ummu Afeera; Cheong, Xiong Khee; Kori, Najma; Abdullah, Shalimar; Chia Hua, Lim; Khalid, Kashfullah; Mohammed Rusli, Emilia Rosniza; Aziz, Muhammad Nazri; Wai-Mun, Leong; Xin Yi, Chew; Abdul Rahman, Ahmad Yamin; Periyasamy, Petrick (Elsevier, 2025)
Mycobacteroides abscessus, a rapidly growing nontuberculous mycobacterium, is known for multidrug resistance and ability to cause chronic infections. Diagnosis can be challenging when standard culture methods fail. Shotgun metagenomic sequencing (mNGS! provides a culture-independent method for identifying pathogens directly from clinical samples. This report details a case of M. abscessus tenosynovitis in a 57-year-old fishmonger following a fish fin injury, where mNGS enabled diagnosis and guided targeted antibiotic therapy after initial cultures and empiric treatments failed.